Airway morphological abnormalities of bronchiolitis assessed by endobronchial optical coherence tomography - Su, Zhu-Quan; Zhong, Ming-Lu; Fan, Ming-Yue; Rao, Wan-Yuan; Zhou, Zi-Qing; Chen, Yu; Chen, Xiao-Bo; Tang, Chun-Li; Zhong, Chang-Hao; Li, Shi-Yue (Therapeutic advances in respiratory disease, 2023)
Background: A few studies have reported the medium-sized and small airway morphological abnormalities of bronchiolitis. Whether spirometry or impulse oscillometry (IOS) is correlated with airway remodeling of bronchiolitis remains unclear. Objectives: Aiming to demonstrate the airway morphological abnormalities of bronchiolitis obliterans (BO) and diffuse panbronchiolitis (DPB) assessed by endobronchial optical coherence tomography (EB-OCT), and elucidate whether spirometric and IOS parameters have correlation with the airway remodeling of bronchiolitis. Methods: We recruited 18 patients with bronchiolitis (BO, n = 9; DPB, n = 9) and 17 control subjects. Assessments of clinical features, St. George’s respiratory questionnaire (SGRQ), chest computed tomography (CT), spirometry, IOS, and EB-OCT were performed in all enrolled subjects. The correlation between EB-OCT and lung function parameters was studied and analyzed. Results: The magnitude of abnormalities of spirometric and IOS parameters was significantly greater in patients with bronchiolitis than that in control subjects (p < 0.05). Patients with BO had notably lower forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC, maximal mid-expiratory flow (MMEF)% pred and higher resonant frequency (Fres), and area of reactance (AX) than those with DPB (p < 0.05). The EB-OCT measurement among patients with bronchiolitis and between the bronchus in the left and the right lung demonstrated a heterogeneous distribution of airway calibers, presenting a high intra- and inter-individual variability. Patients with bronchiolitis had notably greater airway wall area (p < 0.05) compared with control, while BO presented greater magnitude of airway abnormalities than DPB. Fres and the difference in airway resistance at 5 and 20 Hz (R5–R20) correlated negatively with medium-sized and small airway inner area, and correlated positively with airway wall area (p < 0.05), whose correlation coefficients were higher than those of spirometric parameters. Conclusion: Bronchiolitis, BO and DPB, manifested a heterogeneous distribution of airway calibers with significant intra- and inter-individual variability. IOS parameters, rather than spirometry, correlated better with medium-sized and small airway remodeling in bronchiolitis assessed by EB-OCT measurement.